The Characteristics of Human Resources and Related Research Activities among Basic Stem Cell Research Groups in China - Sheng-Jun WANG; Li-Juan LIU; Guang-Yue JI; Xiao-Hua (Andrew) ZHOU; Tian-Jiao JIANG; Mei-Hua LU; De-Lin YU; Qiang GUO; Jin-Hai SUN (Iranian Journal of Public Health, 2019)
Background: This study aimed to evaluate the characteristics of faculty and research activities of basic stem cell research groups in China.